1980
DOI: 10.1073/pnas.77.12.7152
|View full text |Cite
|
Sign up to set email alerts
|

Two interferon mRNAs in human fibroblasts: in vitro translation and Escherichia coli cloning studies.

Abstract: Two mRNA species that produce biologically active interferon were isolated from human fibroblasts and studied by size fractionation and cloning in Escherichia coil plasmid pBR322. The major fibroblast interferon (Hu IFN-B1) is coded for by the smaller of the two mRNAs, an 11S species, 900 nucleotides long, which in cell-free systems yields a 20,000 M, protein. The second interferon mRNA species (Hu is 14S, about 1300 nucleotides long, and codes for another protein of 23,000-26,000 Mr. The two interferon mRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
113
2
4

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(120 citation statements)
references
References 24 publications
1
113
2
4
Order By: Relevance
“…Signal transduction pathways controlling IL-6 gene expression involve activation of protein kinase C as well as cAMP [1]. A tissue specific preferential utilization of distinct initiation sites suggests distinct regulatory mechanisms controlling IL-6 gene expression in different cell species [4,10,11]. Mechanisms that account for differential regulation of the IL-6 gene during ontogeny of a distinct cell type are, however, still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Signal transduction pathways controlling IL-6 gene expression involve activation of protein kinase C as well as cAMP [1]. A tissue specific preferential utilization of distinct initiation sites suggests distinct regulatory mechanisms controlling IL-6 gene expression in different cell species [4,10,11]. Mechanisms that account for differential regulation of the IL-6 gene during ontogeny of a distinct cell type are, however, still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1 clearly shows that WISH cells produced the highest yield of 26-kDa-protein mRNA upon induction. The amount of mRNA is even higher .poly(C) (100 pg/ml, Z h) and cycloheximide (50 pg/ml, 4 h) in these cells than in SV80 cells which were shown previously to produce high levels of this mRNA [6]. MG63, another osteosarcoma cell line, contained similar amounts of the mRNA as WISH cells.…”
Section: Resultsmentioning
confidence: 80%
“…poly(C)-induced and also cycloheximidetreated [6] human fibroblasts an mRNA that is translated in a reticulocyte cell-free system into a 23 -26-kDa protein. This protein can be precipitated with a partially purified antiserum directed against partially purified HuIFN-P. After cloning the corresponding cDNA [6] they could purify this mRNA on its cloned cDNA and translate it into a 23 -26-kDa-protein with antiviral and (2'-5')(A),, synthetase-inducing activities. This protein was named IFN-P, and is probably distinct [7] from the IFN-P, described by Sehgal et al [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it cannot be excluded that the effects observed in our experiments could be partly due to cytokines secreted by the fibroblasts as a result of TNF stimulation. For example, IL-l or TNF-stimulated fibroblasts produce interferon& (IFN-,&), a cytokine with antiviral properties [35]. However, we have recently shown that purified IFN-fl2 was without effect on both collagen and PGE2 formation by fibroblasts (unpublished).…”
Section: Sds-page Analysis Of Radiolabelled Collagens and Fibronectinmentioning
confidence: 99%